Relevansi Kitab Majmu'ul Al-Mirats Fil Hukmil Faraid Karya Haji Ismail Mundu Dengan Materi Pendidikan Islam Kelas XII - Boini, Boini; Mahrus, Erwin (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to determine the relevance between Islamic inheritance law material and the book Majmu'ul Al-Mirats Fil Hukmil Faraid in class XII PAI material. This research was conducted by qualitative methods with a phenomenological approach that is happening today. The focus of this research will be to review the extent of the relevance of the book to PAI material in grade XII high school. The setting of this research was conducted at SMA Negeri 2 Nanga Pinoh, Melawi Regency. Researchers took samples of PAI teaching materials used during teaching and learning activities. The results of the study found that Ismail Mundu as a scholar had practiced his knowledge in educating the community and realizing a religious and peaceful society. Islam regulates human relations with others, which includes the issue of inheritance. Prophet Muhammad (peace be upon him) brought Islamic inheritance law to change the jahiliyah inheritance law which was largely determined by tribal elements that were considered unjust. In Islamic inheritance rules, the curriculum in the world of education also does not escape to review clearly the basic principles concerning inheritance law, so that inheritance material is poured in the high school level learning package book. The Book of Majmu'ul Al-Mirats Fil Hukmil Faraid is very relevant to the PAI material in class XII, because it also explains the source or basis of inheritance law in it and presents the division and example cases in the material content